Using Google Bard to improve secondary school students’ essay writing performance / Shirley Ling Jen and Abdul Rahim Salam - Ling Jen, Shirley; Salam, Abdul Rahim (Universiti Teknologi MARA, Kedah, 2024)
Writing is one of the main language skills assessed in English KSSM syllabus. It constitutes 50% of the overall lower secondary school English exam papers and 25% of the 1119 English paper. Despite all the efforts taken to teach writing, students’ writing performance is still beyond satisfaction. This is because many teachers have employed teacher-centred method in teaching writing. Furthermore, with the revolution of information technology there is a need to integrate technological tools into teaching of writing. One of them is through the use of Google Bard. Thus, this study was carried out to examine the usefulness of Google Bard in improving students’ essay writing performance. Students’ perceptions regarding the use of Google Bard were also collected through journal entries, participant observation, questionnaire and interview. The findings show that students showed favourable responses towards the use of Google Bard in improving their essay writing performance. The paired T-Tests conducted show that there are significant improvements in the experimental group post-test compared to pretest in terms of content, communicative achievement, organisation and language. This is because Google Bard does not only help students with generalisation of ideas and new vocabulary, it also provides flexibility for them to learn at their own pace. Hopefully, Google Bard will also be widely practised in other aspects of language teaching.